Monetary policies and independence of the central banks in E7 countries - Dinçer, Hasan, 1982- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines the effectiveness of the monetary policies and the independence of the central banks in 7 emerging economies"--